الشخصية المركزية في الرحلة العلمية بين سلطان الأنا و صورة الآخر فتح الإله و منته لأبي راس الجزائري نموذجا - حسيني, الطاهر (My University, 2015)
الرحلة فن من الفنون السردية تتحرك داخلها شخصيات تتفاوت أهميتها وقيمتها بالنسبة للسرد والأحداث فيها ورغم واقعية هذه الشخصيات إلا أن الدراسات الحديثة أصبحت تنظر إليها بمنظار فني يدعم ما يعرف اليوم عند النقاد أدبية الرحلة من هنا يأتي هذا المقال ليقف عند تمظهرات الأنا وتجليات صورة الآخر من خلال الشخصية المركزية في الرحلة العلمية انطلاقا من فتح الإله ومنته لأبي راس الجزائري. Peregrination is one of the prose arts in which some personages move upon their importance and value with reference to narrative and events. And though the realistic side of these personages, modern studies deal with them by an aesthetic view which supports what is known at critics as " the literary of peregrination ". From this point this article aims to show the different figures of self characters and the Image of the other through studying the main personage in the scientific Peregrination from " FATH AL ILAH" to ABOURASSALJAZAIRI.
Keywords: سلطان الأنا، صورة الآخر، فتح الإله و منته، أبي راس الجزائري; self characters, Image of the other, FATH AL ILAH, ABOURASSALJAZAIRI